Professional killers: The role of extracellular vesicles in the reciprocal interactions between natural killer, CD8+ cytotoxic T‐cells and tumour cells. Issue 6 (1st April 2021) - Del Vecchio, Filippo; Martinez‐Rodriguez, Verena; Schukking, Monique; Cocks, Alexander; Broseghini, Elisabetta; Fabbri, Muller
Abstract: Extracellular vesicles (EVs) mediate the cross‐talk between cancer cells and the cells of the surrounding Tumour Microenvironment (TME). Professional killer cells include Natural Killer (NK) cells and CD8+ Cytotoxic T‐lymphocytes (CTLs), which represent some of the most effective immune defense mechanisms against cancer cells. Recent evidence supports the role of EVs released by NK cells and CTLs in killing cancer cells, paving the road to a possible therapeutic role for such EVs. This review article provides the state‐of‐the‐art knowledge on the role of NK‐ and CTL‐derived EVs as anticancer agents, focusing on the different functions of different sub‐types of EVs. We also reviewed the current knowledge on the effects of cancer‐derived EVs on NK cells and CTLs, identifying areas for future investigation in the emerging new field of EV‐mediated immunotherapy of cancer.